In vitro and in vivo activity of a hypotoxic copper(I) complex against dermotropic leishmania species - Pereira, Antonia Maria Ramos Franco; Brasil, Anny Maíza Vargas; Correa, Carolina Nunes Souza; Nascimento, Thaís Pinto; Porchia, Marina; Chagas, Ana Flávia Da Silva (Acta Amazonica, 2021)
Cutaneous leishmaniasis is a disease caused by protozoa of the genus Leishmania and, currently, the treatment of first choice is meglumine antimoniate. However, due to its limited effectiveness and high toxicity, it is necessary to seek new active principles for leishmaniasis treatment. Metal complexes are gaining importance due to their effectiveness and low toxicity. In this context, the present study aimed to evaluate the in vitro and in vivo antileishmanial activity of the hypotoxic copper(I) complex [HB(pz)3 ]Cu(PCN). Four dermotropic species of Leishmania were tested with the metal complex and its effectiveness was determined through parasitic viability and infectivity rate, and cytotoxicity was determined using a redox dye (resazurin). For the in vivo tests, hamsters were infected and the lesions treated with a formulated ointment containing the complex, the effectiveness of which was assessed by measuring the diameter of the inoculum/snout location and determining the parasitic load. The results demonstrated moderate toxicity in murine macrophages and human monocytes and better efficacy in Leishmania (V.) braziliensis when compared to the other species tested, with a 50% reduction in the viability of promastigote and amastigote forms (in vitro). General data from daily topical treatment for up to 30 days showed low efficacy for reducing lesions, and no clinical and parasitological cure was observed in the experimental animals. Thus, the [HB(pz)3 ]Cu(PCN) complex proved to be promising in in vitro studies against L. (V.) braziliensis, and should be further tested in new formulations and new experimental treatment schemes. © 2021, Instituto Nacional de Pesquisas da Amazonia. All rights reserved.
Atividade in vitro e in vivo de um complexo de cobre(I) hipotóxico contra espécies dermotrópicas de leishmania
Keywords: Antileishmanial activity; Leishmaniasis